2018
DOI: 10.1111/jog.13722
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoiled cord can cause a reversible abnormal Doppler in ductus venosus in cases of fetal growth restriction

Abstract: Temporary DV-RAV is suspected to be related to the combination of a hypercoiled cord and oligohydramnios. DV-RAV may not be always be a terminal finding in FGR with a hypercoiled cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Ductus venosus is not only the main distributor of fetal oxygenated blood flow, but also the direct channel between peripheral vein and central venous system. Its change can indirectly evaluate the degree of fetal intrauterine hypoxia [ 28 ]. In our study, we found that ductus venosus S/a increased significantly in FGR group, which may be related to the decline of cardiac diastolic function, the increase of venous ductus reflux resistance and the decrease of blood flow in FGR.…”
Section: Discussionmentioning
confidence: 99%
“…Ductus venosus is not only the main distributor of fetal oxygenated blood flow, but also the direct channel between peripheral vein and central venous system. Its change can indirectly evaluate the degree of fetal intrauterine hypoxia [ 28 ]. In our study, we found that ductus venosus S/a increased significantly in FGR group, which may be related to the decline of cardiac diastolic function, the increase of venous ductus reflux resistance and the decrease of blood flow in FGR.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the umbilical cord bloodflow disturbance, which was caused by umbilical cord compression secondary to entire or local oligohydramnios arising from umbilical cord complications (such as a hypercoiled cord and a single umbilical artery), contributed to the severe condition of the patients. Takahashi et al and Iwagaki et al reported an improvement in abnormal UA and DV Doppler findings after administration of AI in cases with FGR with oligohydramnios and umbilical cord complications [4,8]. Repetitive umbilical cord compression induces fetal asphyxia [4,10], and AI relieves umbilical cord compression, decreases the vascular resistance of UA, increases umbilical venous blood flow, and improves oxygenation and the intrauterine environment [9].…”
Section: Discussionmentioning
confidence: 99%
“…Amnioinfusion (AI) is effective for treating variable decelerations in the fetal heart rate caused by umbilical cord compression with oligohydramnios [5,6]. AI has also been reported to improve abnormal fetal Doppler Open Access *Correspondence: katsuo14@belle.shiga-med.ac.jp 1 Department of Obstetrics and Gynecology, Shiga University of Medical Science Hospital, Otsu 520-2192, Japan Full list of author information is available at the end of the article velocity in cases of FGR with oligohydramnios [4,7,8] and in those with umbilical cord compression without oligohydramnios [9]. However, the guidelines for managing FGR and umbilical cord compression using AI are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Due to chronic obstruction of the circulation and hence chronic fetal hypoxia, a longer umbilical cord with overcoiling is associated with intrauterine fetal growth restriction [1,2,5]. The 190-cm-long umbilical cord in this report is the first review in the literature.…”
mentioning
confidence: 83%